Studi Masyarakat Sosial dalam Persfektif Kelompok Sosial dan Stratifikasi Sosial - Azky Siregar, Ariq; Zahra, Maulida; Rambe, Rahmadani; Novita Marpaung, Zeny (Faidatuna, 2023)
The purpose of this research is to find out about the study of social society in the perspective of social groups and social stratification, humans are social beings, which means that they cannot be separated from other creatures or cannot be separated from other social beings. In this world humans live with groups as they are called social groups. And within a social group there are many different layers of society, this is usually called social stratification. The existence of differences in the layers of society has an impact on the life of the community itself. society has a very big role so that it can be said the success or failure of a role of social strata in achieving goals.